Muslim Society Of Thailand: A Study Of Islamic Resurgence In The Globalisation Era - Charoenwong, Worapong (2011)
This study attempts to understand Muslim society of Thailand in the context of global Islamic resurgence. It investigates the historical background of Muslim society in Bangkok and the Deep South, and examines Islamic resurgence with a focus on the growth of transnational Islamic consciousness and Muslim civil society in Thailand. Islamic resurgence in Thailand is part of the larger process of global Islamic resurgence which emerged under the conditions of globalisation. Globalisation has intimate relations with the rise of Islamic consciousness. It accelerates the growth of Islamic consciousness to dramatic rapidity and Islamic resurgence that extends its reach throughout the world produces a globalising trend, that is, the global Islamic resurgence.